EXCITATION AND PROPAGATION OF A FAST PULSE GUIDED WAVE IN A CIRCULAR DIELECTRIC WAVEGUIDE - Legenkiy, M. M.; Butrym, A. Yu. (Видавничий дім «Академперіодика», 2013)
It is shown that a pulse signal in a circular dielectric waveguide is partitioned into slow and fast waves. The fast wave propagatesalong the dielectric surface with the speed of light in free space and creates a precursor field in the dielectric waveguide in theform of cones similar to Cherenkov radiation. These cones are re-reflected at the critical angle between the dielectric interfacescreating a rhombus-shaped wave structure. Long time modeling of this fast wave has been conducted using the Moving FrameBody of Revolution FDTD technique (BOR-FDTD). The revealed peculiarities of the considered wave structure are discussed.